1983
DOI: 10.1111/j.1532-5415.1983.tb04851.x
|View full text |Cite
|
Sign up to set email alerts
|

Earlobe Creases in a Cohort of Elderly Veterans

Abstract: Two‐hundred thirty‐four residents (220 male, 14 female) of a Veterans Administration Nursing Home and a Hospital Based Home Care program, 24–99 years old (mean 66), were examined for the presence (or absence) of earlobe creases and their correlation with cardiovascular disease. Unilateral or bilateral earlobe creases were found in 119 patients (55 unilateral, 64 bilateral), or 50.85 per cent. One hundred forty‐two patients had one or more forms of cardiovascular disease: 20 had coronary artery disease, 45 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…[5,17] However, some other studies have found no such associations and have concluded that the prevalence of ELCs probably increases with age, as does heart diseases. [18,19] Davis et al [12] reported that the sensitivity and specificity of ELC for detecting CAD were 60% and 48%, respectively, and ELC is not associated with CAD. Rhoads and Yano [20] also found no association between ELC and CAD in Japanese-Americans living in Hawaii.…”
Section: Discussionmentioning
confidence: 98%
“…[5,17] However, some other studies have found no such associations and have concluded that the prevalence of ELCs probably increases with age, as does heart diseases. [18,19] Davis et al [12] reported that the sensitivity and specificity of ELC for detecting CAD were 60% and 48%, respectively, and ELC is not associated with CAD. Rhoads and Yano [20] also found no association between ELC and CAD in Japanese-Americans living in Hawaii.…”
Section: Discussionmentioning
confidence: 98%
“…A few reports have dismissed the value of this sign as a marker of CAD. Some studies completely denied this association, and the others explained it as based solely on the increase in the prevalence of both ELC and CAD with advancing age [8, 9, 10, 11]. Overfield and Call [15] reported that ELC developed with age in healthy adults, and the frequency of occurrence of different earlobe shapes differs by race.…”
Section: Discussionmentioning
confidence: 99%
“…However, even studies using coronary angiograms to define CAD presented conflicting results, which could, in part, reflect differences in the criteria for the presence of CAD at angiography [2, 4, 8]. Most of the studies have shown an increased prevalence of ELC with advancing age, and some studies explained the relation between ELC and CAD with advancing age [10, 11, 21]. Miric et al [22]found that ELC indicates an additional risk for myocardial infarction in man below the age of 60 years, independent of age and other coronary risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations